Study of Effectiveness of using different traps with different trap heights of fruit flies (Diptera:Tephritidae) in citrus crops - Maya Soraya; Marheni Marheni; Hasanuddin Hasanuddin (Universitas Sumatera Utara, 2019)
Fruit flies are an important pest of oranges, the damage caused by fruit flies can result in miscarriage in the fruit before reaching the desired maturity. This research was aimed to find out the effectiveness of the use of various traps on fruit fly. The most effective trap was a trap of, combination mixture of methyl eugenol and cocoa waste, a yellow trap at an altitude of 100 cm (142 fruit flies). The use of traps was able to trap male fruit flies and female fruit flies and was able to trap other insects. Other insects trapped were the order Diptera and Coleoptera. Keywords : Fruit fly, pest trap, citrus plants.